The association between obesity and vitamin D deficiency modifies the progression of kidney disease after ischemia/reperfusion injury - Desiree Rita Denelle Bernardo; Daniele Canale; Mariana Moura Nascimento; Maria Heloisa Massola Shimizu; Antonio Carlos Seguro; Ana Carolina de Bragança; Rildo Aparecido Volpini (Frontiers in Nutrition, 2022)
Acute kidney injury (AKI) alters renal hemodynamics, leading to tubular injury, activating pathways of inflammation, proliferation, and cell death. The initial damage caused to renal tissue after an ischemia/reperfusion (I/R) injury exerts an important role in the pathogenesis of the course of AKI, as well as in the predisposition to chronic kidney disease. Vitamin D deficiency has been considered a risk factor for kidney disease and it is associated with tubulointerstitial damage, contributing to the progression of kidney disease. Obesity is directly related to diabetes mellitus and hypertension, the main metabolic disorders responsible for the progression of kidney disease. Furthermore, the expansion of adipose tissue is described as an important factor for increased secretion of pro-inflammatory cytokines and their respective influence on the progression of kidney disease. We aimed to investigate the influence of vitamin D deficiency and obesity on the progression of renal disease in a murine model of renal I/R. Male Wistar rats underwent renal I/R surgery on day 45 and followed until day 90 of the protocol. We allocated the animals to four groups according to each diet received: standard (SD), vitamin D-depleted (VDD), high fat (HFD), or high fat vitamin D-depleted (HFDV). At the end of 90 days, we observed almost undetectable levels of vitamin D in the VDD and HFDV groups. In addition, HFD and HFDV groups presented alterations in the anthropometric and metabolic profile. The combination of vitamin D deficiency and obesity contributed to alterations of functional and hemodynamic parameters observed in the HFDV group. Moreover, this combination favored the exacerbation of the inflammatory process and the renal expression of extracellular matrix proteins and phenotypic alteration markers, resulting in an enlargement of the tubulointerstitial compartment. All these changes were associated with an increased renal expression of transforming growth factor β and reduced expression of the vitamin D receptor. Our results show that the synergistic effect of obesity and vitamin D deficiency exacerbated the hemodynamic and morphological changes present in the evolution of renal disease induced by I/R.